К вопросу о происхождении лексем жадность, заочно, заочный, заслуга, злость в русском языке - Плвловна Гарбуль, Людмила (Slavistica Vilnensis, 2004)
The article examines the origin and the history of the words жадность, заочно, заочный, заслуга, злость found in diplomatic correspondence from Muscovite Russia of the 17th century. The author argues that these derivatives are Polonisms, and that заочно, заочный, заслуга, and злость were borrowed into the Russian written language of the 16th and 17th centuries through ruthenian language.